Current Experience with Obstetrical Events: Characteristics and the Effects of Nocturnal Periods - Susana Blanco-López; Laura Peteiro-Mahía; Rocío Navas-Arrebola; Noelia López-Castiñeira; Sonia Pertega-Díaz; Teresa Seoane-Pillado (IMR Press, 2024)
Background: The object is to analyze the influence of the nocturnal period and lunar phases on the frequency of obstetrical events in pregnant women. Methods: This was a retrospective, transversal observational study of 1409 births in a hospital from northwest Spain (α = 0.05; precision = ±2.65%). A review of patients' clinical records was performed recording the following data: labor onset type, date of last menstrual period, parity, gestational age, duration of pre-labor and labor, type of delivery, the hour, work shift, and lunar phase pattern of events. Statistical evaluation included descriptive and inferential analysis. Results: Labor was spontaneous in 58.3% of all cases; spontaneous deliveries accounted for 54.2% of the total and 19.2% were instrumental. In the cases of spontaneous labor onset, 48.5% began during the nocturnal period. The early labor phase was less than 6 hours in 62.7% of cases (44.8% during the full moon phase). During the nocturnal period, rupture of membranes and dilation periods of less than 3 hours were more common, with 32% of spontaneous membrane rupture occurring during a full moon. A significant dependence was observed between the labor type and nocturnal period, as 40.8% of all spontaneous births, 36.2% of instrumental births and 46.9% of emergency cesarean sections occurred during the night shift. Furthermore, 66.3% of precipitous deliveries (<3 hours) took place during this period. Conclusions: The nocturnal period is related to a higher number of spontaneous rupture of the membranes, non-intervention in the onset of labor, shorter early labor phases, faster deliveries, spontaneous births and emergency caesarean sections. A higher frequency of spontaneous rupture of the membranes, a full labor, early labor phases of less than 3 hours and emergency caesarean sections was observed during full moon phases.